부추 추출물의 PCSK9 억제를 통한 LDL 콜레스테롤 저감 효능 - 최효경(Hyo-Kyoung Choi); 김효진(Hyo Jin Kim); 황진택(Jin-Taek Hwang); 정민유(Min-Yu Chung) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
Accumulation of excess low density lipoprotein (LDL) cholesterol in the blood can initiate and accelerate atherosclerosis. Statins mediate the transactivation of proprotein convertase subtilisin/kexin type 9 (PCSK9), which in turn limits their cholesterol-lowering effects via LDL receptor (LDLR) degradation. The objective of this study was to investigate whether or not Allium tuberosum (AT) regulates LDLR and PCSK9. Mice were fed a low fat control diet (LD) or Western diet (WD) supplemented with AT (1%, w/w). AT significantly attenuated total and LDL cholesterol levels in mice fed WD (P<0.05). AT also significantly inhibited hepatic PCSK9 gene expression (P<0.05) while AT maintained hepatic LDLR gene expression. To further investigate AT-mediated PCSK9 regulation, HepG2 cells were treated with 10% delipidated serum (DLPS) in the presence or absence of AT. Non-toxic level of AT dose-dependently increased the LDLR protein level, and AT at $400μg/mL$ markedly inhibited PCSK9 protein expression. Similarly, AT significantly increased LDLR gene expression, whereas it significantly down-regulated PCSK9 gene expression. AT-mediated reduction of PCSK9 gene expression is likely due to decreased hepatic nuclear factor $1α$ ($HNF1α$) expression, but not SREBP2 in HepG2 cells under lipid-depleted conditions. AT-mediated PCSK9 inhibition contributed to LDLR protein stabilization via protection against LDLR lysosomal degradation in HepG2 cells under lipid-depleted conditions. Further investigation is warranted to determine the active components of AT and whether or not these components are effective in reducing hypercholesterolemia. 본 연구에서는 부추 추출물(Allium tuberosum, AT) 보충식이(1%, w/w)를 12주간 고지방 식이와 함께 마우스에 제공하였다. Western diet(WD)군의 마우스는 low fat diet(LD)군의 마우스보다 유의적으로 높은 총 콜레스테롤 및 LDL 콜레스테롤 수치를 보였으며, 이는 AT 보충식이에 의하여 유의적으로 감소하였다. 또한, 마우스 간 조직 내 PCSK9 유전자가 AT에 의해 유의적으로 감소하였다. 이를 통해 AT의 PCSK9 억제를 통한 LDL 콜레스테롤 저감 가능성을 확인하였다. HepG2 세포주를 지방 부족 환경으로 만들고 AT를 처리하여 PCSK9과 LDLR, 그리고 관련 단백질 및 유전자의 조절 정도를 평가하였다. 그 결과 독성 없는 농도의 AT는 LDLR 단백질 발현을 농도 의존적으로 증가시켰으며, 특히 $400μg/mL$의 AT는 PCSK9 단백질 발현을 억제하였다. 유사하게 AT는 LDLR 유전자 발현량을 유의적으로 증가시켰고, PCSK9의 발현량은 유의적으로 감소시켰다. PCSK9의 억제는 SREBP2가 아닌 AT에 의해 유의적으로 감소한 $HNF1α$ 전사인자 때문이다. AT에 의한 LDLR 유전자의 SREBP2-independent 한 조절은 추후 연구가 필요하다. 다음으로 PCSK9 억제제인 AT의 LDLR 단백질 degradation 및 단백질 합성 조절을 평가하기 위해 지방 제거 상태의 HepG2 세포에 lysosomal degradation inhibitor인 BA1과 단백질 합성 억제제인 CHX를 처리하여 LDLR 단백질 발현 변화를 관찰하였다. AT($400μg/mL$)는 LDLR 단백질의 합성 억제를 block 하였고, 이는 LDLR의 lysosomal degradation을 막음으로써 이루어짐을 알 수 있었다. PCSK9 억제는 고콜레스테롤 혈증이나 콜레스테롤 저항성 치료 혹은 예방 소재 개발에서 중요한 타깃이 될 수 있으며, 부추와 같은 PCSK9 억제 활성을 지닌 천연물 혹은 식품 소재의 발굴이 기존의 치료와 병행하여 또는 독립적으로도 쓰일 수 있는 안전한 소재로써 제안될 수 있다. 추후 동물 실험에서 부추 추출물 및 활성 성분의 PCSK9 활성 억제 연구 및 나아가 부추의 PCSK9 억제를 통한 콜레스테롤 저감 효능 임상 연구 등이 제안될 수 있겠다.